Akuisisi Bukti Digital Aplikasi Pesan Instan “Bip”Menggunakan Metode National Institute Of Justice (NIJ) - Soni Soni; Yulia Fatma; Rizki Anwar (Universitas Muhammadiyah Riau, 2022)
Abstract In the development of the industrial revolution 4.0, information is increasingly showing a great influence on human life. Smartphone technology is often used to access social media and the internet. The development of smartphones, social media, and the number of internet users in the world, especially in Indonesia, are currently being misused, one of which is crime (cybercrime), such as online prostitution, human trafficking, cyberbullying, fraud, extortion, trafficking in illegal goods, drug trafficking. Cyberbullying is an act of intentionally and repeatedly attacking, insulting, or harming other people on social media, instant messenger applications or in other ways that lead to insulting SARA. The NIJ method is a method that aims to explain how the research steps will be carried out so that the flow and research steps can be identified systematically so that they can be used as guidelines for solving existing problems. The NIJ method can be applied in uncovering cases of deleted chat messages. The process of obtaining digital evidence of deleted messages from the instant messaging application